Comparison of Three Scores of Collateral Status for Their Association With Clinical Outcome: The HERMES Collaboration. Issue 12 (17th October 2022) - Gensicke, Henrik; Al-Ajlan, Fahad; Fladt, Joachim; Campbell, Bruce C.V.; Majoie, Charles B.L.M.; Bracard, Serge; Hill, Michael D.; Muir, Keith W.; Demchuk, Andrew; San Román, Luis; van der Lugt, Aad; Liebeskind, David S.; et al.
Abstract : Background: Leptomeningeal collateral status on baseline computed tomographic angiography (CTA) is associated with clinical outcome after acute ischemic stroke treatment. However, assessment of collateral status is not uniform. To compare 3 different CTA collateral scores (CS) and imaging techniques about their association with clinical outcome. Methods: Pooled analysis of patient-level data from the Highly Effective Reperfusion Using Multiple Endovascular Devices collaboration. Patients with large vessel occlusion from 7 randomized controlled trials that compared endovascular thrombectomy with standard medical care were included. Three different CS (Tan CS, regional CS [rCS], and regional Alberta Stroke Program Early CT Score CS) and 2 imaging techniques (single-phase [sCTA] and multiphase/dynamic CTA) were evaluated. Functional independence (modified Rankin Scale score 0–2) at 3 months poststroke was the primary outcome. Furthermore, we assessed the effect of sCTA image acquisition time on collateral status assessment using an adjusted ordinal logistic regression model to obtain predicted values for the trichotomized rCS. Results: Among 1147 pooled patients, 948 (82.7%) had sCTA and 199 (17.3%) multiphase/dynamic CTA as baseline angiography. With all 3 collateral scales, better CSs were associated with better 3-month functional outcome. With sCTA images, the rCS (area under the curve [AUC] 0.63) and regional Alberta Stroke Program Early CT Score CS (AUC 0.62) better predicted functional outcome than the Tan CS (AUC 0.60, respectively; P <0.001 and P =0.02). With multiphase/dynamic CTA images, all collateral scales performed similarly in predicting functional outcome (rCS [AUC 0.61]; regional Alberta Stroke Program Early CT Score CS [AUC 0.61] versus Tan CS [AUC 0.61], respectively; P =0.93 and P =0.91). Overall, no endovascular thrombectomy treatment effect modification by collateral status (rCS) was demonstrated ( P =0.41). sCTA timing independently influenced CS assessment. On earlier timed sCTA, the predicted proportions of scans with poor collaterals was higher and vice versa. Conclusions: In this data set of highly selected patients with stroke, using a regional CS on sCTA likely allows for the most accurate prediction of functional outcome while on time-resolved CTA, the type of CS did not matter. Patients across all collateral grades benefit from endovascular thrombectomy. sCTA timing independently influenced CS assessment.